(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
In today’s world the role of leadership in the control factors of the organization different and advancement, and that the possession of the human ability to the development and creation and innovation varies from one individual to another depending on experience; and levels of performance and intellectual; and his mental and physical and other such factors can create a kind of differentiation between the built humans, and this distinction creates our leaders are able to influence others and have the wisdom and connect active individuals and organizations. as the need for organizations of all sizes and levels of leadership transformation is an urgent need to link the application of the various plans and strategies device which direction does it aware of the pragmatic style in the leadership and move the factors of organizational, cultural, and to ensure its success in the strategic environment.